The effect of feedback by using optical means in some variables biomechanics and effectively push weight for beginners - Ghadban, Yahya (Journal of Physical Education, 2014)
The importance of research of the mechanical aspects of effective performance payment weight by referring to correct postural instantaneously and immediately through Visual observation to match the performance of mechanical conditions that the teacher or tutor, which originally identified the nature of the required information for mechanical event to promote learning for beginners in institutes of physical education for integrates technical performance and the Mechanic, achieving the goal of the educational process. The research aims to identify the level of technical performance and biomechanics variables to effectively push weight to my research. as well as the use of computers as a means for correcting mechanical information to effectively push weight for the experimental group. The influence of the development of mechanical variables for my research. Applied research on randomly chosen sample of students of teachers ’ colleges in Khanaqin were 20 students, divided into two officer and pilot, and then the researcher tests tribal groups and video imaging performance pay, and extracted speed and angle of departure and approach angles and pay, and then apply your tutorial with visual feedback. And search results has been an evolution in all mechanical variables and the development in the achievement